Use of next‐generation sequencing for the identification and characterization of Maize chlorotic mottle virus and Sugarcane mosaic virus causing maize lethal necrosis in Kenya. (10th October 2012) - Adams, I. P.; Miano, D. W.; Kinyua, Z. M.; Wangai, A.; Kimani, E.; Phiri, N.; Reeder, R.; Harju, V.; Glover, R.; Hany, U.; Souza‐Richards, R.; Deb Nath, P.; et al.
<x xml:space="preserve">Abstract</x> The diagnosis of novel unidentified viral plant diseases can be problematic, as the conventional methods such as real‐time PCR or ELISA may be too specific to a particular species or even strain of a virus, whilst alternatives such as electron microscopy (EM) or sap inoculation of indicator species do not usually give species level diagnosis. Next‐generation sequencing (NGS) offers an alternative solution where sequence is generated in a non‐specific fashion and identification is based on similarity searching against GenBank. The conventional and NGS techniques were applied to a damaging and apparently new disease of maize, which was first identified in Kenya in 2011. ELISA and TEM provided negative results, whilst inoculation of other cereal species identified the presence of an unidentified sap transmissible virus. RNA was purified from material showing symptoms and sequenced using a Roche 454 GS‐FLX+. Database searching of the resulting sequence identified the presence of Maize chlorotic mottle virus and Sugarcane mosaic virus, a combination previously reported to cause maize lethal necrosis disease. Over 90% of both viral genome sequences were obtained, allowing strain characterization and the development of specific real‐time PCR assays which were used to confirm the presence of the virus in material with symptoms from six different fields in two different regions of Kenya. The availability of these assays should aid the assessment of the disease and may be used for routine diagnosis. The work shows that next‐generation sequencing is a valuable investigational technique for rapidly identifying potential disease‐causing agents such as viruses.